2021
DOI: 10.1007/s11557-021-01674-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved strategies to efficiently isolate thermophilic, thermotolerant, and heat-resistant fungi from compost and soil

Abstract: Thermophilic, thermotolerant and heat-resistant fungi developed different physiological traits, enabling them to sustain or even flourish under elevated temperatures, which are life-hostile for most other eukaryotes. With the growing demand of heat-stable molecules in biotechnology and industry, the awareness of heat-adapted fungi as a promising source of respective enzymes and biomolecules is still increasing. The aim of this study was to test two different strategies for the efficient isolation and identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…due to low similarity with reference material (Table 4), which might, therefore, represent novel-undescribed species. Yeast is an important part of the microbiota observed during composting because of their ability to decompose dry recalcitrant acid and low-nitrogen-containing substrates in comparison to bacteria [3,5]. As many studies have shown the evolution of the fungal community in the process of composting, Saccharomycetales yeast is associated with the early stages of composting [4].…”
Section: Its-rdna Gene Sequencing Results and Identification Of 6 Yea...mentioning
confidence: 99%
See 1 more Smart Citation
“…due to low similarity with reference material (Table 4), which might, therefore, represent novel-undescribed species. Yeast is an important part of the microbiota observed during composting because of their ability to decompose dry recalcitrant acid and low-nitrogen-containing substrates in comparison to bacteria [3,5]. As many studies have shown the evolution of the fungal community in the process of composting, Saccharomycetales yeast is associated with the early stages of composting [4].…”
Section: Its-rdna Gene Sequencing Results and Identification Of 6 Yea...mentioning
confidence: 99%
“…Yeast has a very important role in life and is present in the fermentation process of food processing [1]. In organic waste treatment, yeast has also been shown to play an important role in the fermentation process that breaks down organic waste [1,3]. Treatment of organic waste by microbial fermentation is a new technology with many outstanding advantages compared to other methods such as landfilling and incineration.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated fungal species from poplar wood chips were classified as known thermophilic taxa, comprising members from Ascomycota, Mucoromycota and mycelia sterilia. The most abundant species, A. fumigatus, R. pusillus and T. lanuginosus, are ubiquitous and common species of thermophilic and thermotolerant fungi described in precedent studies in different wood chip types, diverse substrates (compost, mulch, soil) and different locations [14,34,[44][45][46]. In addition, most of the cultivated taxa are known to produce (ligno)cellulolytic enzymes, e.g.…”
Section: Methodsmentioning
confidence: 99%